The effect of fiber intake on the association of pesticide exposure and hypertension: a population-level study - Lai, Haili; Xin, Xiaoqin (Frontiers in Public Health, 2025)
The association between pesticide exposure and the risk of hypertension is inconsistent. Moreover, little is known about the effects of dietary fiber intake on the association between pesticide exposure and the risk of hypertension. This study aimed to assess whether fiber intake alters the relationship between pesticide exposure and hypertension. The study included 14,218 American adult patients. Multivariate logistic regression analysis was used to assess the relationship between pesticide exposure and the risk of hypertension. We also examined the relationship between pesticide metabolites in urine specimens and hypertension. Participants were stratified based on their mean fiber intake (low fiber intake: <17 gm and high fiber intake: ≥17 gm). An interaction test between dietary fiber intake, pesticide exposure, and risk of hypertension was conducted. Exposure to pesticides increased the risk of hypertension in the crude and full-adjusted models, and their odds ratio (ORs) [95% Confidence Interval (CI)] were 1.40 (1.26–1.56) and 1.19 (1.05–1.34), respectively. The analysis of pesticide metabolites indicated that dimethyldithiophosphate was statistically associated with hypertension (OR = 1.01, 95% CI = 1.01–1.02). The association between pesticide exposure and hypertension was opposite among participants in low and high fiber intake groups, OR = 1.34, 95% CI: 1.14–1.58 vs. OR = 0.98, 95% CI: 0.80–1.20, respectively, which implied that a high fiber intake may decrease the risk of hypertension (interaction likelihood ratio test: p = 0.031). We are the first to report the role of fiber intake in pesticide exposure and the risk of hypertension.